Kajian Banjir Daerah Aliran Sungai Cilaki Cianjur-Garut - Noni Nuraeni; Sulwan Permana (Jurnal Konstruksi, 2026)
The Cilaki River stretches from upstream Pangalengan - Talegong to its downstream at the Cilaki bridge, the longest bridge in South Garut. According to BPBD volunteers on December 25, 2021, the Cilaki River Cianjur - Garut experienced very high rainfall which resulted in flooding that closed the main route connecting between regencies in Kertajadi Village, Cidaun District, Cianjur Regency, West Java Province submerged in floods as high as one meter. Therefore, this research aims to identify the planned flood discharge and analyze the inundation area in the Cilaki watershed using the HEC-RAS application, with the simulation results used to determine the level of flood vulnerability. The methods used include field surveys, hydrological analysis for the calculation of flood discharge according to the watershed area using the HSS Nakayasu method, and prediction of water levels through HEC-RAS for estimation of inundation area. The results showed a peak discharge at the 6th hour with a discharge of 403.17 m³/sec for a 25-year return period, 415.35 m³/sec for 50 years, and 424.58 m³/sec for 100 years. The inundation area reached 13,190 ha at the 25-year return period, 15,003 ha at 50 years, and 16,700 ha at 100 years.